Genocide in Jewish thought - Patterson, David, 1948- (Cambridge; New York : Cambridge University Press, 2012)
"Among the topics explored in this book are ways of viewing the soul, the relation between body and soul, environmentalist thought, the phenomenon of torture, and the philosophical and theological warrants for genocide. Presenting an analysis of abstract modes of thought that have contributed to genocide, the book argues that a Jewish model of concrete thinking may inform our understanding of the abstractions that can lead to genocide. Its aim is to draw upon distinctively Jewish categories of thought to demonstrate how the conceptual defacing of the other human being serves to promote the murder of peoples, and to suggest a way of thinking that might help prevent genocide"--
Introduction: a name, not an essence -- 1. Why Jewish thought, and what makes it Jewish? -- 2. Deadly philosophical abstraction -- 3. The stranger in your midst -- 4. Nefesh: the soul as flesh and blood -- 5. The environmentalist contribution to genocide -- 6. Torture -- 7. Hunger and homelessness -- 8. Philosophy, religion, and genocide -- A concluding reflection on body and soul.
Includes bibliographical references (p. 231-246) and index.
Description based on print version record.
Keywords: Genocide -- Philosophy; Thought and thinking -- Philosophy; Jewish philosophy; Humanity -- Philosophy; Jewish ethics -- Philosophy; Philosophy and religion; Holocaust, Jewish (1939-1945); Hebrew language -- Roots; RELIGION / Judaism / General; RELIGION / Judaism / Theology; Electronic books